Adipose-Derived Stem Cells Promote Intussusceptive Lymphangiogenesis by Restricting Dermal Fibrosis in Irradiated Tissue of Mice - Ogino, Ryohei (Int J Mol Sci, 2020)
Currently, there is no definitive treatment for lymphatic disorders. Adipose-derived stem cells (ADSCs) have been reported to promote lymphatic regeneration in lymphedema models, but the mechanisms underlying the therapeutic effects remain unclear. Here, we tested the therapeutic effects of ADSC transplantation on lymphedema using a secondary lymphedema mouse model. The model was established in C57BL/6J mice by x-irradiation and surgical removal of the lymphatic system in situ. The number of lymphatic vessels with anti-lymphatic vessel endothelial hyaluronan receptor 1 (LYVE-1) immunoreactivity increased significantly in mice subjected to transplantation of 7.5 × 10(5) ADSCs. X-irradiation suppressed lymphatic vessel dilation, which ADSC transplantation could mitigate. Proliferative cell nuclear antigen staining showed increased lymphatic endothelial cell (LEC) and extracellular matrix proliferation. Picrosirius red staining revealed normal collagen fiber orientation in the dermal tissue after ADSC transplantation. These therapeutic effects were not related to vascular endothelial growth factor (VEGF)-C expression. Scanning electron microscopy revealed structures similar to the intraluminal pillar during intussusceptive angiogenesis on the inside of dilated lymphatic vessels. We predicted that intussusceptive lymphangiogenesis occurred in lymphedema. Our findings indicate that ADSC transplantation contributes to lymphedema reduction by promoting LEC proliferation, improving fibrosis and dilation capacity of lymphatic vessels, and increasing the number of lymphatic vessels via intussusceptive lymphangiogenesis.